Integration of InSAR and deterministic coefficient methods to study the disaster susceptibility of transmission tower slope - Bo Hu; Chaoyang Shan (Geomatics, Natural Hazards & Risk)
In order to prevent and maintain the stability of transmission line slope disaster more effectively, this paper first puts forward the combination of InSAR technology and deterministic coefficient method. This study takes the transmission tower of Muzengke North Line in Guangzhou, China as the research object, and obtains 45 scene SAR data. Small Baseline Subset (SBAS) time series analysis algorithm is used to investigates it using the surface displacement. The importance of landslide influencing factors is evaluated by using deterministic coefficient method, and the disaster susceptibility of evaluation unit is evaluated. Results show the overall line is stable, yet potential risk areas exist, especially near transmission tower construction areas, with a maximum annual average settlement rate of - 113mm/yr, and a large subsidence risk along the G15 - G17 tower points of Line 2. Among the four influence factors, the sensitivity order is elevation > slope > relief > slope direction. By analyzing the slope disaster susceptibility, this study reveals displacement characteristics, key monitoring areas, and main landslide factors. In this study, the idea of combining multi-temporal InSAR analysis and deterministic coefficient method is proposed for the first time, which provides a basis for the safety management and early warning of transmission line towers.